New 2D roughness parameters with geometric and physical meanings for rock joints and their correlation with joint roughness coefficient - He, Cheng; Tang, Huiming; Fang, Kun; Sun, Sixuan (Frontiers in Earth Science, 2024)
Determining the joint roughness accurately will better serve the peak shear strength estimation models of rock joints used for stability assessment of rock masses. Considering the defects of the existing quantitative characterization parameters for two-dimensional (2D) joint roughness, especially the lack of explicit geometric and physical meaning, we proposed two new 2D roughness parameters, θ 2D and h 2D . The former, θ 2D , represents the average inclination angle of all potential contact asperities over the entire joint profile, while the latter, h 2D , characterizes their average undulation height. Both parameters are closely related to the shear strength of rock joints. Then, the roughness parameters θ 2D and h 2D of 102 rock joint profiles digitized at 0.5 mm sampling interval were calculated, and a new nonlinear regression equation for the determination of the 2D joint roughness coefficient (JRC) was established by combining the calculated results of the two roughness parameters. It was verified that the proposed equation could give accurate JRC estimation values of the 10 standard profiles of rock joints. Through the comparative analysis of the experimental data collected from earlier studies for the peak shear strength of 73 rock joint samples and corresponding estimated values, the equation was further verified to be applicable and accurate for estimating the JRC values of rock joints. Furthermore, we discussed the effects of shear direction and sampling interval on roughness and further provided another equation that could be applied to estimate the JRC values of joint profiles at the sampling interval of 1.0 mm.